Development of Automatic Solar Tracking System for Small Solar Energy System - Mohamud Ahmed, Musse; Kamrul Hasan, Mohammad; Shafiq, Mohammad (International Journal of Engineering and Technology, 2018)
The main purpose of this paper is to present a novel idea that is based on design and development of an automatic solar tracker system that tracks the Sun's energy for maximum energy output achievement. In this paper, a novel automatic solar tracking system has been developed for small-scale solar energy system. The hardware part and programming part have been concurrently developed in order for the solar tracking system to be possible for it to operate accurately. Arduino Uno R3, Sensor Shield V4 Digital Analog Module, LDR (Light Dependent Resistor), MPU-6050 6DOF 3 Axis Gyroscope has been used for tracking the angular sun movement as shown in Fig. 1. Accelerometer, High-Efficiency Solar Panel, and Tower Pro MG90S Servo Motor have been used for the hardware part. High-level programming language has been embedded in the hardware to operate the tracking system effectively. The tracking system has shown significant improvement of energy delivery to solar panel comparing to the conventional method. All the results will be shown in the full paper. There are three contributions the research presented in this paper which are, i.e. perfect tracking system, the comparison between the static and tracking system and the development of Gyroscope angular movement system which tracks the angular movement of the sun along with another tracking system.Â Â